Make in India by Reviving Investment, Manufacturing and Job Creation - Kumar, Vikas (Journal of Commerce and Trade, 2015)
The economic policy of the government in its first year has been focused on reforms, infrastructure, ease of doing business to revive investment, for manufacturing sector growth for job creation. Though it’s to early to measure outcomes of these policies, the future of Indian economy certainly looks bright. The launch of eBiz portal for businesses is one of the technology enabled e-governance efforts. The eBiz portal is a single-window system on the web for firms to navigate the documentationrelated formalities of setting and managing a business in India. As of now, eleven services can be availed online in G2B eBiz portal. The government aims to integrate 26 central government services across nine departments on the platform. The government has rightly identified the problem and focused on the manufacturing sector on a mission mode. The government’s ‘Make in India’ scheme basically announces to the world that India is better place to invest in than before, that the government is doing what it can to ease the rules and simplify procedures, while investing in physical infrastructure. The huge increase in untied resources would give states the fiscal space to design their own developmental schemes and programs according to their specific circumstances. However, there is also apprehension about the use of money by the States as the quality and capacity of state administration varies widely and therefore, the increased untied fiscal transfers along with reduction in tied developmental plan schemes may lead to misuse of money.